The Influence of Knowledge Purchasing Decisions - Nadya, Vivin Tri; Maknunah, Lu' Lu Ul (Universitas Islam Balitar, 2024)
One of the sectors in which economic development occurs in Indonesia is the agricultural sector. Fruit is one of the gems of home gardening. Durian is one of the best fruits found in Indonesia. A company that grows plants vegetatively, such as cuttings, branches, paste, grafts, and tissue culture, is known as a fruit seedling company. The goal of the fruit plant nursery in Pagergunung Village, Kesamben District, Blitar Regency, is to supply the fruit seed needs of the producers. This study employs a questionnaire-based survey research design. Interviews and observations have revealed that UD. Tiga Putri Buah has thirty clients, many of them are durian seed buyers. Since there were only 100 respondents in this study, the author included all 100 participants. Results of some research: Purchasing decisions (Y) are negatively or negatively impacted by business knowledge (X).